Analysis Of The Urgency Of Euthanasia Regulation In Indonesia - Fadhila, Kharisma Wulan; Noerdajasakti, Setiawan; Kurniaty, Rika (CV. AFDIFAL MAJU BERKAH, 2024)
This study aims to discuss the urgency of regulating euthanasia in Indonesia. This study uses a type of normative legal research using research methods on laws and regulations, conceptual approaches and comparative legal approaches. The results of this study show that various arrangements for euthanasia in Indonesia are very embraced, to realize laws and regulations, not only in the field of criminal law, but also regulated in health law about euthanasia in accordance with the circumstances and situations that will occur in the future